Optimalisasi Teknologi Google Sites untuk Profil dan Potensi Desa: Pengabdian Masyarakat di Desa Semambung Kecamatan Kayen Kidul Kabupaten Kediri - Huda, M Thoriqul; Moh. Luthfi Kusyairi; Tiko Budianto; Faridh Alfi Ramadhan; Rusli Ahmad Annashir; Muhammad Rafly Ali; Diana Ashilla Sari; Nurliska Wati Azyzah; Popy Ayu Irmayanita; Irma Roudlotul Jannah; Nur Aula Sholikhatul Afifa; Nadia Ariani Kurnia Putri; Tarisa Adinda; Giska Nurani; Lela Ade Luftiana; Nurul Fatin Karimah; Sofie Nur Hafidah (Subservire: Jurnal Pengabdian Masyarakat, 2025)
This community service program was motivated by the limitations of Semambung Village, Kayen Kidul District, Kediri Regency, which, until mid-2025, had no digital-based media to present its village profile and potential. The program aimed to assist the village in creating an effective, efficient, and easy-to-manage profile website using the free Google Sites platform. The method employed was descriptive with a Participatory Action Research (PAR) approach, involving collaborative stages of problem identification, planning, implementation, and evaluation with village officials. Data were collected through interviews, observation, and documentation, and analyzed qualitatively in a descriptive manner. The results show that the village profile website was successfully developed and populated with essential information such as demographic data, economic potential, community activities, and public services. Challenges included unstable internet connectivity, limited initial digital skills among village officials, and the feature limitations of Google Sites compared to professional platforms. Nevertheless, the resulting website effectively improved public information transparency and served as an online promotional tool for the village’s potential. The implication of this program is the creation of a digital mentoring model that can be replicated in other villages with similar conditions, thus accelerating digital transformation at the village level.